Irrigation and nitrogen management of African (Siphonochilus aethiopicus (Schweinf.) B.L. Burtt) and commercial ginger (Zingiber officinale Roscoe) - Marais, Diana (University of Pretoria, 2020)
Thesis (PhD)--University of Pretoria, 2019.